2022
DOI: 10.1155/2022/6705052
|View full text |Cite
|
Sign up to set email alerts
|

Nontherapeutic Risk Factors of Different Grouped Stage IIIC Breast Cancer Patients’ Mortality: A Study of the US Surveillance, Epidemiology, and End Results Database

Abstract: Objectives. Stage IIIC breast cancer, as a local advanced breast cancer, has a poor prognosis compared with that of early breast cancer. We further investigated the risk factors of mortality in stage IIIC primary breast cancer patients and their predictive value. Methods. We extracted data from the US Surveillance, Epidemiology, and End Results (SEER) database of female patients with stage IIIC primary breast cancer (n = 1673) from January 2011 to December 2015. Results. Hormone receptor negativity ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Prognosis and related indicators of different diseases are the focus of current research (26)(27)(28)(29). Our model could accurately identify high risk of death within 5 years of surgery in non-small cell lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prognosis and related indicators of different diseases are the focus of current research (26)(27)(28)(29). Our model could accurately identify high risk of death within 5 years of surgery in non-small cell lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The research on the factors related to the prognosis of various diseases is the current research focus (36)(37)(38)(39). It is suggested that Dabuyin pill can inhibit the development of secondary sexual characteristics, reduce the volume of the uterus and ovaries, slow down the speed of bone maturation, and has no adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The research on the prognosis and related biological indicators of different diseases is the focus of current research (26)(27)(28)(29)(30). The parameters of breast dynamic enhancement MRI in young breast cancer patients are specific, which is manifested by an increased proportion of patients with non-mass enhancement, a decrease in the ADC, and is related to the clinical features and prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%